Hepatitis C in South Australia And Northern Territory: A Population-Based Linkage Study - Stephens, Jacqueline H; Bradley, Clare; Elliott, Salenna; Dore, Gregory; Grebely, Jason; Alavi, Maryam; Kennedy, Brendan; Tong, Steven; Ward, James (International Journal of Population Data Science, 2020)
Introduction In Australia, the notification rate for hepatitis C is 5 times greater among Aboriginal and Torres Strait Islander peoples than non‑Indigenous populations (164 vs. 35 per 100,000). Infection with Hepatitis C virus is associated with increased morbidity, mortality and health-related costs. Recently, the use of simple, tolerable and short-duration HCV therapies with extremely high efficacy (cure rates >90%) became available through the Pharmaceutical Benefits Scheme (PBS) on 1 March 2016. Objectives and Approach Overall, this project aims to identify inequities in hepatitis C healthcare for Aboriginal and Torres Strait Islander peoples across SA and NT. By using 19 routinely collected health administration datasets, we will evaluate hepatitis C diagnoses, treatment uptake, and treatment outcomes, with focus on identifying patterns in healthcare access among Aboriginal and Torres Strait Islander people. The study links state-based and federal datasets, including Medicare, Pharmaceutical Benefits Scheme, and National Mortality Database, to hepatitis C notifications reported in SA since 1992 or in NT since 1999 using probabilistic data linkage methodology in a secured online environment. Results The study population includes all hepatitis C notifications recorded in SA and NT, totalling more than 25,000 cases. Preliminary findings will be reported including incidence of hospitalisation, mortality, and morbidity by Aboriginal and Torres Strait Islander status. Conclusion / Implications This project is of national importance to address hepatitis C related morbidity and mortality in Australia, particularly among Aboriginal and Torres Strait Islander peoples. Now that highly effective direct acting anti-viral treatments are available, it is crucial to ensure key affected populations, including Aboriginal and Torres Strait Islander people, have access to these novel biomedical approaches. Findings will underpin future policy to reduce the burden of hepatitis C across SA and NT populations.